Autorregulación y éxito académico con estudiantes de la institución educativa secundaria César Augusto Vargas Ramírez de Vista Alegre 2024 - Arimuya Tapullima, Sarai (2025)
The objective of this study was to determine the degree of relationship between self regulation and academic success among students at the César Augusto Vargas Ramírez secondary school in Vista Alegre 2023. The question was: How does self control impact students' ability to excel academically? The type and design of the study was quantitative, correlational, and non experimental. Of the 78 students, 100% participated as a sample. In other words, it was a census. The descriptive analysis showed that the responses were divided into three categories: low, average, and high, with the average category being the most prevalent based on Spearman's correlation coefficient. The inferential analysis highlights a strong positive correlation between self-regulation and academic performance. The p-value of the test statistic was 0.01, so Ho is rejected in favor of Ha. The HG is based on the conclusion that self-regulation is regularly correlated with academic performance at the Cesar Augusto Vargas Ramírez secondary school in Vista Alegre 2023. The results were consistent across both variables, indicating that fostering self regulation in students is a crucial factor in achieving academic success and a healthy relationship with the school environment. It is therefore advisable to encourage the active participation of families in the school process, as this can facilitate the development of self-regulation skills in students. It is recommended that talks be held with parents and guardians to educate them about the importance of self-control and ways to help their children develop these skills.